Early and high-volume administration of sodium bicarbonate in sepsis-associated acute kidney injury in patients with malignancies, during continuous renal replacement therapy - Lamei Ouyang; Yin Pan; Ya-Fei Wu; Qiang Tang; Dao-Feng Wang; Ning Lou (Renal Failure)
Introduction Sepsis is an uncontrolled systemic response to infection that leads to life-threatening organ dysfunction. The in-hospital mortality rate remains significantly high in septic shock patients with malignancies. This study investigates whether early and high-volume administration of sodium bicarbonate during continuous renal replacement therapy (CRRT) can reduce 28-day mortality, increase shock reversal rates, and shorten the duration of CRRT, mechanical ventilation, and intensive care unit (ICU) stays. The goal is to provide valuable clinical data for the management of cancer patients with sepsis-associated acute kidney injury (SAKI).Materials and methods A retrospective study was performed on 88 patients who were admitted to the ICU and received continuous renal replacement therapy (CRRT) for acute renal failure secondary to sepsis at the Cancer Center of Sun Yat-sen University from March 2010 to October 2021. Based on the initiation time of CRRT and the volume of sodium bicarbonate infusion, patients were divided into four groups: the early high-volume group, early low-volume group, late high-volume group, and late low-volume group.Results The results of this study showed that in the 28-day mortality model, established using the Cox proportional hazards method, early CRRT (HR 0.473; 95% CI 0.245–0.915, p = 0.026) and high-volume sodium bicarbonate infusion (HR 0.173; 95% CI 0.078–0.383, p < 0.001) were identified as two independent protective factors. The 28-day mortality rate in the early high-volume group (15.0%) was significantly lower than that of the other three groups (60.0%, 30.0%, and 75.0%, respectively; χ2 = 23.822, p < 0.001). Additionally, the shock reversal rate in the early high-volume group (80.0%) was significantly higher compared to the other groups (35.0%, 45.0%, and 35.7%; χ2 =13.576, p = 0.004). The duration of CRRT was shorter in the early high-volume group (35.0 ± 4.45 h) than in the other groups (70.0 ± 30.19 h, 48.0 ± 5.22 h, and 72.0 ± 19.84 h; χ2 =11.278, p = 0.01). Furthermore, the duration of mechanical ventilation (7.0 ± 3.33 days) was lower in the early high-volume group compared to the other groups (8.0 ± 1.12 days,10.0 ± 1.11 days, and 8.0 ± 2.65 days; χ2 =8.064, p = 0.045), as was the length of ICU stay (7.0 ± 0.89 days) compared to the other groups (13.0 ± 3.35 days, 10.0 ± 1.49 days, and10.0 ± 3.70 days; χ2 = 9.184, p = 0.027).Conclusion Early and high-volume administration of sodium bicarbonate during CRRT may reduce 28-day mortality and improve shock reversal rates in patients with sepsis-associated acute kidney injury complicated by malignancy. Prospective randomized controlled large sample studies are needed to confirm this.